The optimal starting point for survival time in pulmonary metastasectomy. (July 2016) - Kamiyoshihara, Mitsuhiro; Igai, Hitoshi; Ibe, Takashi; Kawatani, Natsuko; Yoshikawa, Ryohei
Aim: Studies of metastatic lung cancer have used various starting points for calculating the survival period, including the time of primary tumor resection and the first and final pulmonary metastasectomy. This study examined differences in prognostic factors according to the starting point used to calculate survival time. Methods: We performed surgical resection of pulmonary metastases in 202 consecutive patients between 1999 and 2013. Of these, 146 (excluding overlapping cases) underwent pulmonary metastasectomy. We examined the survival period after resection in patients with pulmonary metastases (group M) and primary tumors (group P). The prognostic influence of variables on survival was analyzed. Results: The 5-year survival rate was 76.7% in group P and 62.0% in group M. The significant prognostic factors were the disease-free interval (>1 and >2 years) in group P, and maximum tumor diameter in group M. Interestingly, multivariate analysis showed that the significant prognostic factors (age and nodule diameter) were identical in both groups. Conclusions: We believe that the potential confounding factors were counterbalanced by the effect of prognostic factors on multivariate analysis in patients undergoing pulmonary metastasectomy. If the survival period is defined as starting from the time of the primary tumor resection, this may resolve the variance in survival, because pulmonary metastasectomy is only one option among several available treatments.